PENGENDALIAN WAKTU DAN ANGGARAN BIAYA PADA PROYEK PEMBANGUNAN BANGUNAN PENGENDALI SEDIMEN BATANG KURANJI DAN ANAK SUNGAINYA (SEGMEN HULU) KOTA PADANG DENGAN METODE EARNED VALUE - Nasrul Nasrul; Sintia Sintia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The main resources limited to the implementation stage of a construction project are cost, quality and time. Planning, schedule and control are important steps to take in order for the objectives of the implementation of this project with limited resources to be achieved. The